Kepastian Hukum Aset Kripto sebagai Instrumen Investasi dalam Persfektif Hukum Islam dan Hukum Positif - Siregar, Emiel Salim; Manurung, Widya; Gunawan, Rudi; Dzulkhairil, Muhammad; Siagian, Ramadhan; Ardiansyah, Muhammad; Lubis, Rusdi; Sitorus, Andreansyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Cryptocurrency is a virtual currency without physical form or concrete existence in the virtual world. One of them is Crypto Assets, which are becoming increasingly popular as a means of online payment, even though the government has banned it. In early 2019, the Indonesian government issued regulations legalizing Crypto Assets in Commodity Futures Trading. The use of Crypto Assets as commodities and exchange tools in online transactions has sparked pros and cons among religious scholars and economic experts. This study aims to determine the status of cryptocurrency as a commodity in Indonesia and the opportunities for Crypto Assets as subjects in Sharia commodities on the Commodity Exchange. The theory used is the theory of valid and invalid business transactions in Islam. This research is a literature study and qualitative in nature. The data analysis technique used is analytical descriptive with a normative juridical Islamic law approach. The research found that cryptocurrency can be traded in Sharia commodity exchanges with the condition that the country must protect the trade with legal umbrella and issue cryptocurrency with its value based on gold or the country's currency. Crypto Assets cannot be used as commodities in Sharia Derivative Contracts in Indonesia because they still contain speculation, maysir, and are vulnerable to being used for illegal activities. Therefore, Crypto Assets are haram due to external factors, so it is best to avoid them.